2021
DOI: 10.3390/electronics10172064
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Deep Learning Model for Potato Leaf Disease Recognition

Abstract: Potato leaf disease detection in an early stage is challenging because of variations in crop species, crop diseases symptoms and environmental factors. These factors make it difficult to detect potato leaf diseases in the early stage. Various machine learning techniques have been developed to detect potato leaf diseases. However, the existing methods cannot detect crop species and crop diseases in general because these models are trained and tested on images of plant leaves of a specific region. In this resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(46 citation statements)
references
References 45 publications
(68 reference statements)
0
22
0
Order By: Relevance
“…In this study, the shortcomings of the PlantVillage dataset were verified, and the PBD-IM dataset was established by data enhancement. By comparing the methods proposed by other researchers in Table 5 , the accuracy rate of the model in this study is 0.06% and 5.81% higher than the models proposed by Rashid et al [ 34 ] and Afzaal et al [ 35 ], respectively. In terms of data enhancement, Chen et al [ 37 ] used a generative adversarial network (GAN) to automatically synthesize diverse images with a 2.08% lower accuracy rate than the generic data enhancement and weather data enhancement methods proposed in this study.…”
Section: Experimental Results and Analysismentioning
confidence: 53%
See 1 more Smart Citation
“…In this study, the shortcomings of the PlantVillage dataset were verified, and the PBD-IM dataset was established by data enhancement. By comparing the methods proposed by other researchers in Table 5 , the accuracy rate of the model in this study is 0.06% and 5.81% higher than the models proposed by Rashid et al [ 34 ] and Afzaal et al [ 35 ], respectively. In terms of data enhancement, Chen et al [ 37 ] used a generative adversarial network (GAN) to automatically synthesize diverse images with a 2.08% lower accuracy rate than the generic data enhancement and weather data enhancement methods proposed in this study.…”
Section: Experimental Results and Analysismentioning
confidence: 53%
“…Table 5 reviews the work related to this study. Most of the image data used to detect potatoes' early and late blight came from the PlantVillage dataset, while Rashid et al [ 34 ] and Afzaal et al [ 35 ] established their datasets. In this study, the shortcomings of the PlantVillage dataset were verified, and the PBD-IM dataset was established by data enhancement.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…The results of this study were compared with the results of other studies shown in Table 7 . Rashid et al ( 2021 ) and Mathew and Mahesh ( 2022 ) used the same dataset as this study. The accuracy of all these studies is lower than the model presented in this article.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the feasibility of deep learning algorithms based on an encoder-decoder architecture for semantic segmentation of potato late blight spots based on field images, Gao et al ( 2021 ) used a SegNet-based encoder-decoder neural network architecture for lesion segmentation, which can extract semantic features from low to high level, in a disease test dataset with leaves and soil in the background to intersect and union (IOU) values of 0.996 and 0.386, respectively. Rashid et al ( 2021 ) proposed a multilevel deep learning model to classify potato leaf diseases called PDDCNN. First, potato leaves were extracted using the YOLOV5 image segmentation technique from potato plant images.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of the one-stage detector are SSD [ 17 ], YOLO [ 18 ], and CenterNet [ 19 ]. These one-stage detectors are not only able to reach high accuracies, but also have a faster processing speed [ 12 ], making them notable in the field of agriculture, where plant images are collected and utilized to classify plant species [ 20 , 21 , 22 ], count plants or fruits [ 23 , 24 ], identify pests [ 25 , 26 , 27 ] and weeds [ 28 , 29 ], and detect diseases [ 26 , 27 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Related Workmentioning
confidence: 99%